MEMBIMBING SISWA MENGEMBANGKAN MINAT MEMBACA: STRATEGI GURU DALAM MENERAPKAN KEGIATAN MEMBACA TERBIMBING DENGAN POJOK BACA DI SD SUKOSARI 01 - Yuni Astutik; Jeffry Handhika; Dwi Rosita Sari (An Nafi': Multidisciplinary Science, 2026)
Reading interest among elementary school students remains a challenge that requires systematic and interesting strategies. This study aims to describe the strategies used by teachers in implementing guided reading activities (Direct Reading Activity) using reading corners to develop fifth-grade students' reading interest. This qualitative research employs a case study design to explore teaching practices in real classroom contexts. The research was conducted at SD Negeri Sukosari 01, Madiun Regency, involving classroom teachers and library teachers. Data were collected through in-depth interviews, participatory observation of reading activities, and analysis of lesson plans and reading corner documentation. Thematic analysis was conducted through data reduction, data display, and conclusion drawing. The findings reveal that teachers develop three strategic approaches: (1) integrating reading corners as an integral part of the learning environment, (2) implementing modified Direct Reading Activity stages according to student characteristics, and (3) creating post-reading activities that connect reading experiences with students' daily lives. These strategies demonstrate teachers' creativity in transforming reading corners from mere physical spaces into interactive literacy learning centers.